2021
DOI: 10.1016/j.jid.2020.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Sunshine: Genetic Predisposition to Sun Seeking in 265,000 Individuals of European Ancestry

Abstract: Despite growing public awareness of the adverse consequences of excessive sun exposure, modifying sunseeking behavior is challenging because it appears to be driven by addictive mechanisms. This can have effects on health because sun exposure, although beneficial, when prolonged and repeated shows a causal relationship with skin cancer risk. Using data from 2,500 United Kingdom twins, we observed sun seeking to be significantly heritable (h2 ! 58%). In a GWAS meta-analysis of sun-seeking behavior in 261,915 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 76 publications
2
7
0
Order By: Relevance
“…This may be because the duration of summer in Europe is not long, and the season is not as sunny or sweltering as in Asia. In addition, tanning behavior has been reported to be commonplace in Europe 8–10 . Consistent with this, our study found that purchases of bronzer/tanning sunscreens were significantly higher in Europe than in the other regions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This may be because the duration of summer in Europe is not long, and the season is not as sunny or sweltering as in Asia. In addition, tanning behavior has been reported to be commonplace in Europe 8–10 . Consistent with this, our study found that purchases of bronzer/tanning sunscreens were significantly higher in Europe than in the other regions.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, tanning behavior has been reported to be commonplace in Europe. [8][9][10] Consistent with this, our study found that purchases of bronzer/tanning sunscreens were significantly higher in Europe than in the other regions. Furthermore, 31% of sunscreens in Europe were labeled reef-safe; this was the highest proportion of the continents…”
Section: Discussionsupporting
confidence: 88%
“…For instance, it has been reported that indoor tanning is associated with mental health problems 54 , physical activity and dietary practices 55 , and other risky behaviours 56, 57 . Moreover, a recent GWAS meta-analysis on sun-seeking behaviour 58 , adjusted for tanning ability and SEP, identified 5 loci related to behavioural traits, including addiction. In our study, additional factors included beliefs about tanning, which were unrelated to genetically-determined pigmentation traits (Supplementary Table 20), and parental education and SEP. Identifying the causes of indoor tanning behaviour warrants further investigation to inform policy and practice.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of D2R levels can produce a decrease of feeling pleasure for usual incentives and a need to compensate for this deficiency, promoting a high risk for multiple addictive, impulsive, and compulsive behaviors overall drugs of abuse (Tsou et al, 2019). Hence, other polymorphisms in the dopamine system, such as the dopamine receptors genes for dopamine receptors type 2, 3, and 4 ( DRD2 , DRD3 , and DRD4 ), the dopamine transporter ( DAT1 ) gene, and enzymes involved in dopamine degradation (catechol‐ o ‐methyl‐transferase, [COMT]) have also a link with addiction and obesity and have been discussed in other review articles (Lindgren et al, 2017; Sanna et al, 2020; S. C. Wang, Chen, Lee, & Cheng, 2019).…”
Section: Genetics Of Vulnerability and Resilience In Addictionmentioning
confidence: 99%